Heritability of social behavioral phenotypes and preliminary associations with autism spectrum disorder risk genes in rhesus macaques: A whole exome sequencing study. Issue 3 (29th January 2022) - Gunter, Chris; Harris, R. Alan; Kovacs‐Balint, Zsofia; Raveendran, Muthuswamy; Michopoulos, Vasiliki; Bachevalier, Jocelyne; Raper, Jessica; Sanchez, Mar M.; Rogers, Jeffrey
Abstract: Nonhuman primates and especially rhesus macaques ( Macaca mulatta ) have been indispensable animal models for studies of various aspects of neurobiology, developmental psychology, and other aspects of neuroscience. While remarkable progress has been made in our understanding of influences on atypical human social behavior, such as that observed in autism spectrum disorders (ASD), many significant questions remain. Improved understanding of the relationships among variation in specific genes and variation in expressed social behavior in a nonhuman primate would benefit efforts to investigate risk factors, developmental mechanisms, and potential therapies for behavioral disorders including ASD. To study genetic influences on key aspects of social behavior and interactions—individual competence and/or motivation for specific aspects of social behavior—we quantified individual variation in social interactions among juvenile rhesus macaques using both a standard macaque ethogram and a macaque‐relevant modification of the human Social Responsiveness Scale. Our analyses demonstrate that various aspects of juvenile social behavior exhibit significant genetic heritability, with estimated quantitative genetic effects similar to that described for ASD in human children. We also performed exome sequencing and analyzed variants in 143 genes previously suggested to influence risk for human ASD. We find preliminary evidence for genetic association between specific variants and both individual behaviors and multi‐behavioral factor scores. To our knowledge, this is the first demonstration that spontaneous social behaviors performed by free‐ranging juvenile rhesus macaques display significant genetic heritability and then to use exome sequencing data to examine potential macaque genetic associations in genes associated with human ASD. Lay Summary: In order to better understand both the genetic mechanisms that cause and possible therapies for treating autism spectrum disorders, it will be valuable to understand how genetic differences among nonhuman primates can influence brain function and resulting differences in social behavior. Rhesus macaques exhibit many complex social behaviors and are amenable to various kinds of genetic analysis, making them a highly relevant animal model. We watched more than 200 rhesus macaques in a naturalistic environment and used two different measures to identify differences among the animals in their expression of various social behaviors. We then used quantitative analyses of the differences among the animals and found that some behaviors were strongly influenced by genetic variation and may be linked to specific DNA sequence variants, just as has been demonstrated in humans.